Serum neuron specific enolase in the prognosis of intracerebral hemorrhage - Berilgen, M. Said; Polat, Nilgün; Bulut, Serpil; Müngen, Bülent (Turkiye Klinikleri, 2005)
Objective: The aim of the study was to investigate whether serum neuron specific enolase (NSE) levels can be utilized as a non-invasive technique to determine early-stage morbidity after acute intracerebral hemorrhage. Material and Methods: 40 patients presenting with acute intracerebral hemorrhage and 20 age and sex-matched healthy volunteers were examined in the Neurology Department of the Firat University Faculty of Medicine. Serum NSE levels at 48 hours, 5 days, and 10 days were analyzed and corresponding clinical status according to the Glasgow Coma Scale were determined. Intracerebral hemorrhage volumes after 48 hours were measured. Clinical status according to functional independence measure (FIM) was determined after 30 days. Results: Positive correlations were seen at 48 hours, 5 days, and 10 days between serum NSE values and intracerebral hemorrhage volumes (r= 0.55, p< 0.001; r= 0.67, p< 0.001; P= 0.57, p< 0.001; r= 0.58, p< 0.001, respectively). In contrast, negative correlations were noted at 48 hours and 5 days between serum NSE levels and clinical condition (r= -0.42, p< 0.01; r= -0.38, p< 0.01, respectively). Conclusion: NSE levels, as a neuro-biochemical marker of post-stroke acute cerebral damage, can be utilized as a non-invasive method of early-stage determination of morbidity following intracerebral hemorrhage. Copyright © 2005 by Türkiye Klinikleri.
İntraserebral kanamanin klinik seyrinde serum nöron spesifik enolaz'in de?eri
Keywords: Cerebral hemorrhage; Neuron specific enolase; Stroke